Sleep Disturbance and Chronic Urticaria: A Narrative Review of Its Relationship, Treatment and Evolving Literature - Asad Ullah Wasim; Sri Anugna Miriyala; Raymond Haward; Zeinab Hammoud; Pratik Agarwal; Nirja Kaka; Neil Patel; Yashendra Sethi; Poonam Gupta (Health Science Reports)
ABSTRACT Background and Aims Chronic Spontaneous Urticaria is characterized by the sudden onset of itchy wheals and angioedema and is primarily driven by mast cells. It can have a significant impact on the Quality of Life (QoL) of an individual. While the role of mast cells in urticaria is extensively described, the link between sleep disorders and inflammatory skin conditions such as urticaria is still being explored. The review aims to provide an overview of the current knowledge about chronic urticaria, elaborating on the impact of poor sleep quality on QoL of patients with urticaria, with a focus on their emotional well‐being. Methods The review explores potential mechanisms linking chronic urticaria and sleep disturbances, such as persistent itching and discomfort, the release of inflammatory mediators, systemic inflammation, psychological factors, and effects of medication. Results The review finds that sleep disturbances have a significant impact on chronic urticaria. It identifies several potential mechanisms linking the two conditions, including persistent symptoms, inflammatory processes, psychological factors, and medication effects. Treatment approaches include a combination of pharmacological and nonpharmacological interventions. Conclusion The article emphasizes the significance of recognizing the impact of sleep disturbances on chronic urticaria. It lays the groundwork for future research to expand our understanding of this association, ultimately leading to improved management strategies and improved QoL for affected individuals.